Evaluating a Usability, User Experience and Accessibility Checklist for Assistive Technologies for Deaf people in a Context of Mobile Applications - de Godoi, Tatiany Xavier; García, Laura Sánchez; Valentim, Natasha Malveira Costa (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
nologies that support Deafs to carry out their daily activities, contributing to their independence and quality of life. However, not all ATs are presented with quality for their users, resulting in abandonment, frustration or incorrect use. To obtain an AT with higher quality, this work presents an AT evaluation technology for Deaf Community, which covers the perspectives of Usability, User eXperience (UX) and Accessibility for mobile devices, entitled Usability, User eXperience, and Accessibility Checklist for Deaf Assistive Technology (UUXAC-DAT). UUXAC-DAT aims to support professionals of Information Technology (IT) during the assessment of ATs in software development projects. To assess UUXACDAT, a case study was carried out, with nine IT professionals. Perceptions of professionals about the ease of use, perceived usefulness and intent for future use of UUXAC-DAT were obtained. All professionals were interviewed and the results were analyzed qualitatively. This paper also presents some improvements in UUXAC-DAT, regarding its structure, description of verification items and presentation.